Outward and inward protection efficiencies of different mask designs for different respiratory activities. (February 2022) - Koh, Xue Qi; Sng, Anqi; Chee, Jing Yee; Sadovoy, Anton; Luo, Ping; Daniel, Dan
Abstract: We evaluate the outward and inward protection efficiencies of different mask types (N95, surgical and two cloth mask designs) taking into account the imperfect fit on the wearer. To this end, we built a manikin to simulate exhaling, coughing and inhaling of aerosol droplets 0.3– 5 . 0 μ m in diameters. The protection efficiencies depend on many factors, including the droplet size, the mask fit and the presence of a filter layer. Here, we show that cloth and surgical masks with a non-woven filter layer can achieve a combined outward and inward protection efficiencies between 50% and 90%. Removing the filter layer greatly reduces the protection efficiency to below 20% for the smallest droplet size. While a well-fitted N95 masks offer protection efficiency close to 100%, a poorly fitted N95 mask with gaps offers less protection than a well-fitted surgical/cloth mask with filter layer. We also found that double masking—the wearing of cloth mask on top of a surgical mask—offers little to no additional protection as compared to a single cloth/surgical mask. The results of our work can inform the implementation of mask mandates to minimize airborne transmissions of coronavirus disease of 2019 (COVID-19). Highlights: Protection effectiveness of masks depends on the flow rates and hence the exact respiratory activity. Cloth mask with non-woven filter layer offers similar protection as surgical mask against airborne transmissions. Double-masking offers little to no additional protection over a single high-quality cloth/surgical mask.